2018
DOI: 10.1080/09540121.2018.1441972
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms in young people with perinatally acquired HIV and HIV affected young people in England

Abstract: Adolescents with perinatal HIV (PHIV) may be at higher risk of anxiety and depression than HIV negative young people. We investigated prevalence of anxiety and depression symptoms in 283 PHIV and 96 HIV-affected (HIV-negative) young people in England recruited into the Adolescents and Adults Living with Perinatal HIV (AALPHI) cohort. We used Hospital Anxiety and Depression Scale (HADS) scores and linear regression investigated predictors of higher (worse) scores.115 (41%) and 29 (30%) PHIV and HIV-affected you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
(67 reference statements)
3
28
1
Order By: Relevance
“…However, studies of PHIV and HIV exposed/affected youth have found broadly similar results to our survey. A recent UK study of PHIV and HIV-affected negative young people, mostly black African with median age 16 years, found a prevalence of moderate/severe anxiety symptoms using HADS of around 15–18% in both groups [10]. Meanwhile in the USA, emotional problems were reported by 17% of HIV-exposed and 12% of PHIV youth in one study [9] while another found a 25% prevalence of any mood disorder among 197 PHIV youth [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, studies of PHIV and HIV exposed/affected youth have found broadly similar results to our survey. A recent UK study of PHIV and HIV-affected negative young people, mostly black African with median age 16 years, found a prevalence of moderate/severe anxiety symptoms using HADS of around 15–18% in both groups [10]. Meanwhile in the USA, emotional problems were reported by 17% of HIV-exposed and 12% of PHIV youth in one study [9] while another found a 25% prevalence of any mood disorder among 197 PHIV youth [37].…”
Section: Discussionmentioning
confidence: 99%
“…Self- or anticipated stigma may be a barrier to disclosure of HIV status to others and to seeking emotional and practical support, and this may become more relevant for the PHIV group as they move away from family in the coming years and navigate disclosure to new friends and partners [43]. The association between lower self-esteem and poorer mental health has been found among PHIV young people elsewhere [10, 44] and in general population samples [45], and is a potential area for intervention; however, even after adjusting for self-esteem, felt stigma remained associated with recent moderate/severe anxiety in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if this were the case one would expect higher prevalence of self-harm or depression in the HIV negative comparison group. The AALPHI comparator group did in fact have higher prevalence of self-harm (19.0% vs. 12.2%) however the difference was not statistically significant ( p = 0.089), and there was no difference in the level of depression between the two groups in a previous analysis [39].…”
Section: Discussionmentioning
confidence: 96%
“…Another possibility is that our study did not detect an effect of depression due to its relationship with self-esteem, which itself was a strong predictor of self-harm. Low self-esteem has been found to both increase an individual’s vulnerability to depression, and to be a symptom of depression [17], and we recently found that lower self-esteem predicted higher depression scores in the AALPHI cohort [39]. Previous research has shown that low self-esteem and depressive symptoms often co-occur among the general population of adolescents [40, 41], although some studies suggest that the direction of the association between self-esteem and depressive symptoms is predominantly from self-esteem to depressive symptoms [42, 43].…”
Section: Discussionmentioning
confidence: 99%